Carrapatos em aves, no ambiente e em animais domésticos em área de cerrado do Triângulo Mineiro, Uberlândia, MG - Pascoal, Jamile de Oliveira (2009)
In Brazil, information on ticks focus on the parasite species of domestic animals while those of wild animals, especially birds, are scarce and fragmented. Based on what was exposed, this study aimed to conduct a survey on the fauna of ticks and assess their importance in wild birds in an area of the cerrado of the Triângulo Mineiro under intense anthropogenic effect, the Natural Reserve of Clube de Caça e Pesca Itororó, Uberlândia, MG, Brazil. Besides assessing the infestation of birds by ticks to establish possible correlations with the environmental infestation and from domestic animals living nearby. Ticks were collected on birds from a small cerrado fragment in the reserve, and also collected from the environment and from domestic animals from neighboring properties. On the whole 238 passarine birds were captured from April 2008 to February 2009. From these 22 were infested with overall 31 ticks. Solely Amblyomma nodosum larvae and nymphs were recovered from these birds. Infestation of ticks host-seeking on the ground level were low and included all stages of Amblyomma cajennense, an Amblyomma dubitatum adult and larvae clusters of Boophilus microplus. Dogs from neighboring properties were infested with Rhipicephalus sanguineus adults, Amblyomma cajennense adults and nymphs, B. microplus nymphs; Horses had adults and nymphs of A. nitens, nymphs of B. microplus, nymph of A. cajennense. Bovines were infested solely with B. microplus (adults and nymphs).